Transportation and urban development in São Paulo: exploring how transportation has shaped and still shapes the city - Costa, Adriano Borges (2018)
When the city sprawls, what came first, transportation or urban development? Can transportation be used to promote urban changes? What kind of changes in the built environment can we expect from transportation investments? Transportation is a critical factor explaining the morphology of an urban area. While historical aspects of transportation can determine the form of cities, new investments may also affect and change the surrounding built environment. The study of urban form and urban transportation is one of the elements that unite the two empirical essays comprising this thesis. Another aspect that recurs among the chapters of this manuscript is empirical analysis based in São Paulo. There is a lack of empirical results evidencing the interconnected development of road transportation and peripheral urban sprawl in São Paulo. In Chapter 1, we used Granger causality models and historical data on transportation and urban development to measure the co-development of these factors in the city between 1881 and 2013. Our findings confirm the hypothesis in the literature by showing that urban sprawl followed road transportation deployment, but this phenomenon also moved in the opposite direction, with sprawl pulling construction of new roadways. We explore how critical juncture decisions made during the 1930’s have prioritized road development instead of mass transit, that after that was no more capable to follow São Paulo’s urban sprawl. Nonetheless, we found evidence that mass transit investments have historically been followed by significant building densification in surrounding areas. In Chapter 2, we developed a short-term empirical analysis using a wider range of variables to explore how recent mass transportation investment is currently changing São Paulo’s neighborhoods, with particular attention to peripheral areas. Since the 1980`s, the urban condition of many peripheral areas has improved significantly, and middle-income families are moving to some of this “upgraded peripheries.” We used highly spatial disaggregated socioeconomic data from 2000 and 2010 and a differences-in-differences econometric method to access the impact of new bus corridors, subway lines, and train stations built in the early 2000s. Our findings show that the accessibility gains generated by these public transportation facilities have attracted new real estate projects, increased the number of jobs per capita, and led to better provision of some public services in surrounding peripheral areas, contributing to their urban consolidation. This result, added to the mentioned historical findings, reveals the potential which transportation investment has to change the built environment, whether by stimulating peripheral urban sprawl, inducing densification, or contributing to urban consolidation. The use of transit investments to induce urban transformations is receiving new attention as the concept of transit oriented development (TOD) attracts more adepts and evident that transportation and urban land use plans must be integrated. The factors are interrelated, and coordinated public interventions therefore have the potential to produce synergistic results. However, mass transit investments are among the most complex urban policies and present specific challenges for public policy studies, primarily related to intra- and inter-federative coordination in their implementation.